1974
DOI: 10.1302/0301-620x.56b3.421
|View full text |Cite
|
Sign up to set email alerts
|

The Fibrinolytic Enzyme System After Trauma and in Patients With Fat Embolism

Abstract: The pathogenesis of fat embolism, a common complication of fractures of the long bones of the lower limbs, is not delineated. Any explanation must take account of the recognised association of intravascular fibrin deposits with fat embolism. The fibrinolytic enzyme system may function to remove unwanted fibrin in the body. were VOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1979
1979
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The changes most frequently described have been the reduction of kalcemia and platelets, the increase of platelet adherence, the prolonged times of activated partial prothrombin and thromboplastin, the release of FDPs (fibrin degradation products), and the reduction of circulating fibrinogen (8,16,17,20,22,24,27,39,74) . Those changes, however, do not occur in all FES cases (27,30,75) and, when they do, are usually subtle (27,76) . Thus, the majority of the recent authors think that laboratory changes suggesting DIVC shall be attributed mainly to coagulation changes that usually accompany a severe trauma than to a potential FES (22,74,75) .…”
Section: Laboratory Changesmentioning
confidence: 94%
See 2 more Smart Citations
“…The changes most frequently described have been the reduction of kalcemia and platelets, the increase of platelet adherence, the prolonged times of activated partial prothrombin and thromboplastin, the release of FDPs (fibrin degradation products), and the reduction of circulating fibrinogen (8,16,17,20,22,24,27,39,74) . Those changes, however, do not occur in all FES cases (27,30,75) and, when they do, are usually subtle (27,76) . Thus, the majority of the recent authors think that laboratory changes suggesting DIVC shall be attributed mainly to coagulation changes that usually accompany a severe trauma than to a potential FES (22,74,75) .…”
Section: Laboratory Changesmentioning
confidence: 94%
“…In fact, it is not uncommon to find laboratorial changes compatible to DIVC syndrome in some cases of FES (22,27,45,74) , yet the occurrence of the hemorrhagic syndrome secondary to this consuming coagulopathy is extremely rare (13) . On the other hand, there are well established FES case series, in which the authors did not manage to detect laboratory changes characterizing DIVC in none of the patients (30,75) . For the great majority of researchers, therefore, DIVC is considered as an infrequent phenomenon, which can or cannot occur in conjunction with FES (13,27,74,76) .…”
Section: "Biochemical Phase"mentioning
confidence: 98%
See 1 more Smart Citation
“…Fibrino lytic activity was higher after surgery or trauma (44). Plasma plasminogen levels were also higher after surgery or trauma (45,46). Low fibrinolytic activity was observed in pregnant women at later months of pregnan cy.…”
Section: Exercise Injury and Pregnancymentioning
confidence: 97%
“…These findings easily lead us to conclude that fat entered the vasculature from the injured bone marrow. Rennie, et al (1974) reported that the changes of the plasminogen level and the platelet count were great in the traumatized patients. Jacobs (1976) found some evidences for intravascular coagulation in experimental dogs.…”
Section: Cases Of Acute Decompression Sicknessmentioning
confidence: 99%